Poet’s Attitudes to Religions in Bhagavadajjuka and Mattavilāsa : a Comparative Study - Tudkeao, Chanwit; Boonyo, Boondarika (Mahachula Academic Journal, 2026)
This article investigates the poet’s attitudes to religions in two Sanskrit prahasana plays, Bhagavadajjuka and Mattavilāsa, by comparatively analyzing religious ideas, doctrines, practices, and modes of religious satire in the texts, together with reconsidering authorship as a key to interpretation. The study employs a qualitative approach, examining Sanskrit originals and translations of both plays alongside related scriptures and literary sources on Sāṅkhya–Yoga philosophy, Buddhism, and Śaivism in India between the fifth and seventh centuries CE. The findings show that Bhagavadajjuka presents an image of a religious mendicant firmly grounded in philosophical teachings—especially those of Yoga—using the vidūṣaka as a foil to contrast “a truly realized ascetic” with “one who merely adopts the outer form of renunciation”, while largely avoiding harsh satire of other religious doctrines. In contrast, Mattavilāsa foregrounds sharp mockery, denunciation, and ridicule of religions, founders, and ascetics from various sects, including Kāpālikas, Pāśupatas, and Buddhists, by emphasizing immoral monks and distorted practices as the main source of comic effect. On the basis of these differing religious perspectives, satirical strategies, and degrees of appreciation for philosophical teachings, the study concludes that the poets of Bhagavadajjuka and Mattavilāsa are unlikely to be the same person, and proposes its analytical framework as a model for future research on other prahasana plays that take religion as their central vastu.